International Multi-Center Analysis of In-hospital Morbidity and Mortality of Low-Voltage Electrical Injuries - Warenits, Alexandra-Maria; Aman, Martin; Zanon, Clara; Klimitz, Felix; Kammerlander, Andreas A.; Laggner, Anton; Horter, Johannes; Kneser, Ulrich; Bergmeister-Berghoff, Anna Sophie; Schrögendorfer, Klaus F.; Bergmeister, Konstantin D. (Frontiers in Medicine, 2020)
Background: Patients with high- and low-voltage electrical injuries differ in their clinical presentation from minor symptoms to life-threatening conditions. For an adequate diagnosis and treatment strategy a multidisciplinary team is often needed, due to the heterogeneity of the clinical presentation. To minimize costs and medical resources, especially for patients with mild symptoms presenting after low-voltage electrical injuries, risk stratification for the development of further complications is needed. Methods: During 2012-2019 two independent patient cohorts admitted with electrical injuries in two maximum care university hospitals in Germany and Austria were investigated to quantify risk factors for prolonged treatment, the need of surgery and death in low-voltage injuries. High-voltage injuries were used as reference in the analysis of the low-voltage electrical injury. Results: We analyzed 239 admitted patients with low-voltage (75%; 276±118V), high-voltage (17%; 12.385±28.896V) or unclear voltage (8%). Overall mortality was 2% (N=5) associated only with high-voltage injuries. Patients with low-voltage injuries presented with electrocution entry marks (63%), various neurological symptoms (31%), burn injuries (at least second degree) (23%), pain (27%), and cardiac symptoms (9%) including self-limiting thoracic pain and dysrhythmia without any therapeutic need. 73% of patients with low-voltage injury were discharged within 24 hours. The remaining patients stayed in the hospital (11±10 days) for treatment of entry marks and burns, with an overall need for surgery of 12% in all low-voltage injuries. Conclusions: The only identified risk factors for prolonged hospital stay in patients with low-voltage electrical injuries were the treatment of burns and electric marks. In this multi-center analysis of hospitalized patients, low-voltage electrical injuries were not associated with cardiac arrhythmia or mortality. Therefore, we suggest that asymptomatic patients, without preexisting conditions, with low-voltage injury can be discharged after an initial check-up without prolonged monitoring.